A NEPOTISM AND CRONY IN A BUSINESS, CASE OF INDUSTRIAL DEREGULATION IN INDONESIA - Efendy, Muhadjir (Universitas Muhammdaiyah Surakarta, 2011)
An industrial deregulation is a government policy in developing a stateâs economic infrastructure. If a country undergoes a process of powerful personalization, its interest is identical with a powerful interest. For an economic profit, the Presidentâs relative and crony do a business and build directly unproductive seeking activities. This study aims to examine the relation of relative to crony in realizing an industrial deregulation in the 1980s and its impact on the Indonesian economy in a view of macroeconomic policy. It focuses on a problem of the industrial deregulation from 1983 to 1990 with economic growth by the indicator of contribution to GDP and labor force. The study used an expose facto approach. The data were the secondary sources: documents, textbooks and mass media. It used a qualitative-descriptive analysis.